1990
DOI: 10.1007/bf02562431
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the new 23‐methyl‐5,9‐pentacosadienoic acid in the spongeCribrochalina vasculum

Abstract: The phospholipid fatty acids from the sponge Cribrochalina vasculum were studied, revealing the presence of the new 23-methyl-5,9-pentacosadienoic acid (26:2) which completes the iso-anteiso 26:2 (delta 5,9) series. Other phospholipid fatty acids isolated include 26-methyl-5,9-heptacosadienoic (28:2) and 25-methyl-5,9-heptacosadienoic (28:2), as well as the branched acids 8-methylhexadecanoic and 11-methyloctadecanoic. The fatty acids described in this work were found in phosphatidylethanolamine, phosphatidyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The C26:2(5, 9) is a major constituent of the FAs of the Demospongiae class. There are species of the Demospongiae class having no or trace amounts of the C26:2 (5,9) [5,7], but there are the species of the Demospongiae class which contain very high amount of C26:2 (5,9) [6,11]. Both specimen of A. carteri of our investigation contained C26:2 (5,9) which constitutes more than 40% of the total FA mixtures.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The C26:2(5, 9) is a major constituent of the FAs of the Demospongiae class. There are species of the Demospongiae class having no or trace amounts of the C26:2 (5,9) [5,7], but there are the species of the Demospongiae class which contain very high amount of C26:2 (5,9) [6,11]. Both specimen of A. carteri of our investigation contained C26:2 (5,9) which constitutes more than 40% of the total FA mixtures.…”
mentioning
confidence: 87%
“…In the literature it is reported that these are the rare acids which were found in Caribbean sponges [9], and it was believed that such acids have bacterial origin [10,11]. So the presence of symbiotic bacteria cannot be excluded.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The principal ones without methylene separation were 26:2(∆5,9), 26:3(∆5, 9,19), 27:2(∆5,9), 28:3(∆5, 9,19), 28:3(∆5, 9,21), and 28:3(∆5, 9,23), which are typical for sponges (Table 1). Other polyunsaturated FA included arachidonic 20:4(∆5, 8,11,14), eicosapentaenoic 20:5(∆5, 8,11,14,17), and docosahexaenoic 22:6(∆4, 7,10,13,16,19).…”
mentioning
confidence: 98%
“…Such acids are usually considered to originate from bacteria [18,19]. Saturated FA with one branching in the middle of the chain, for example, 10-Me-16:0, 10-Me-18:0, 11-Me-18:0, and 13-Me-20:0 were previously found in other sponges [20][21][22][23]. We assume that such acids are synthesized by bacteria associated with the sponges and are very characteristic just for demosponges bacterial symbionts [24,25].…”
mentioning
confidence: 99%